2010
DOI: 10.4103/0022-3859.68633
|View full text |Cite
|
Sign up to set email alerts
|

Association of glutathione S-transferase (GSTM1, T1 and P1) gene polymorphisms with type 2 diabetes mellitus in north Indian population

Abstract: This is the first study showing the association of a combined effect of GSTM1, T1 and P1 genotypes in a representative cohort of Indian patients with T2DM. Since significant association was seen in GSTM1 null and GSTP1 (I/V) and multiple association in GSTM1 null, T1 present and P1 (I/I), these polymorphisms can be screened in the population to determine the diabetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 33 publications
4
33
1
Order By: Relevance
“…The majority of case control studies of GSTM1 and GSTT1 null genotypes have reported risk associations with disease [26,27]. The frequency of the GSTM1 null genotype in our study was 38.61%; it is little lower than reported in other populations (Egyptian 58.62%, Dubai 57.5%, North Indian 54.00%) [28–30]. The frequency of the GSTTI null genotype was 7.92% in T2DM patients, which is lower when compared to the Dubai (60.0%) and Egyptian (35.0%) populations [7,29].…”
Section: Discussioncontrasting
confidence: 57%
“…The majority of case control studies of GSTM1 and GSTT1 null genotypes have reported risk associations with disease [26,27]. The frequency of the GSTM1 null genotype in our study was 38.61%; it is little lower than reported in other populations (Egyptian 58.62%, Dubai 57.5%, North Indian 54.00%) [28–30]. The frequency of the GSTTI null genotype was 7.92% in T2DM patients, which is lower when compared to the Dubai (60.0%) and Egyptian (35.0%) populations [7,29].…”
Section: Discussioncontrasting
confidence: 57%
“…No association was found between GST polymorphisms and BMI in Indian diabetic patients with null and positive GST genotypes. 11,32 Similarly, in Korean schizophrenic patients, no association was observed between GST polymorphisms and druginduced weight gain. 12 In view of these results, it can be concluded that GST polymorphisms are not associated with a higher BMI among hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that GST polymorphisms were not associated with BMI in diabetic North Indians or with weight gain in schizophrenic Koreans. 11,12 Since there is a close link between hypertension and obesity, this study sought to investigate the association of ACE and GST gene polymorphisms with BMI among a selected group of hypertensive North Indians.…”
mentioning
confidence: 99%
“…Although, high intraocular pressure (IOP) is recognized as being the main risk factor, the pathophysiology of POAG is considered multifactorial and multiple theories have been issued: mechanical damage due to high IOP, vascular dysregulation, altered intracranial pressure dynamics, glutamate excitotoxicity, nitric oxide dysregulation, astrocite reactivation, extracellular matrix remodelling, mutations in specific genes, changes in the mitochondrial genome, blood-retinal barrier breakdown and secondary low-grade inflammation, toxic effects and oxidative damage caused by reactive oxygen species (ROS) (3,10).…”
Section: To the Editormentioning
confidence: 99%